The Tourism of Titillation in Tijuana and Niagara Falls: Cross-Border Tourism and Hollywood Films between 1896 and 1960 - Brégent-Heald, Dominique (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2006)
AbstractIn the popular imaginary, Tijuana, Mexico is notorious for its liberal laws concerning prostitution, gambling, and narcotics. Conversely, Niagara Falls, Canada apparently offers visitors only wholesome attractions. Yet this sweeping generalization belies the historic parallels that exist between these iconic border towns. In Hollywood films, both Tijuana and Niagara Falls figure as liminal locations of crossing and collision, as well as permissive zones defined by sex, tourism, and consumption. This essay explores the intertwined cultural arenas of film and tourism by analyzing cinematic representations of Tijuana and Niagara Falls as cross-border tourist destinations. By examining how cinematic representations of these urbanized border regions have changed over time, I demonstrate how Hollywood, as a hegemonic culture industry, responded to the United States’ evolving relationships with its northern and southern neighbors. This study offers a hemispheric and comparative approach to the study of urban borders, tourism, and visual culture.